SLC35A2 is a novel prognostic biomarker and promotes cell proliferation and metastasis via Wnt/β-catenin/EMT signaling pathway in breast cancer - Rushu Yan; Tianwen Chen (Scientific Reports)
Abstract Although it is a leading cause of cancer-related mortality among women globally, breast cancer (BC) has drawn increased attention owing to its poor prognosis and the challenges associated with limited treatment options. SLC35A2 was shown to be dysregulated in a number of tumor types according to multiple investigations. However, its function in BC was rarely reported. This study aims to investigate the expression of SLC35A2 in BC and its impact on the functionality and prognosis of BC cells. We collected 11 pairs of BC tissues and normal specimens, obtaining clinical information from 1,118 BC patients through RNA sequencing analysis. Different BC cell lines were used in experiments, and the roles of SLC35A2 in cell proliferation, invasion, and migration was assessed through gene silencing and functional assays. Additionally, a prognostic model, including SLC35A2 expression levels, age, T-stage, M-stage, N-stage, and clinical stage, was constructed, and its predictive performance in overall survival was validated using time-dependent receiver operating characteristic curves. High SLC35A2 expression was correlated positively with patient age and T-stage. Kaplan-Meier survival curves and Cox regression analysis confirmed the independent and significant prognostic value of SLC35A2 in overall survival. Functional experiments demonstrated that SLC35A2 silencing inhibited the proliferation, migration, and invasion of BC cells, affecting their metastatic potential through modulation of the Wnt/β-catenin/EMT signaling pathway. In conclusion, our study reveals the crucial role of SLC35A2 in BC, providing a novel biomarker for clinical management and valuable insights into the underlying mechanisms of BC pathogenesis.